ANALYSIS OF BEKASI RIVER TO FLOOD IN PONDOK GEDE PERMAI HOUSING - Fakhri Jauhar Akbar Bima Putra; Jantiara Eka Nandiasa (NAROTAMA UNIVERSITY, Indonesia, 2021)
The Bekasi River flow that crosses Pondok Gede Permai Housing is a river network that flows in the housing of Pondok Gede Permai. With a good river flow system, economical and as needed from housing, the passing water flow is expected to flow smoothly according to the dimensions that have been taken into account. The methodology done in this research is a descriptive analysis of evaluative is a method that evaluates the objective conditions in a situation that becomes the object of research and the object of the study, the flow of rivers surrounding the housing Pondok Gede Permai. From the results of this research can be concluded that the cause of flooding in Pondok Gede Permai housing is caused by the confluence of two currents between the Cikeas river flow and the Cileungsi River. And also because of the widespread water from the river Cikeas to the Bekasi River, and because the meeting between the two rivers of Bekasi and Sunagi Cikeas are very small.